Simulink Methods to Simulate COVID-19 Outbreak Using Fractional Order Models (Contemporary Mathematics, 2024)
The objective of this work is to solve a coronavirus transmission model using Simulink, a platform for model-based design that facilitates simulation and design at the system level. The simulation is divided into two sections: the first deals with setting up the parameters, and the second deals with computing the fractional derivatives. The fundamental susceptible-infected-removed (SIR), susceptible-exposed-infected-recovered (SEIR), susceptible-exposed-infected-isolated-recovered (SEIQR), and susceptible-exposed-infected-asymptotically infected-recovered-reservoir (SEIARM) models were used in this study. An effective, quick, easy, and visually appealing method is used to simulate pandemic outbreaks. To accurately follow the progress of the infection, we contrast the simulation findings with those acquired by MATLAB code. The applications can be used for research projects and as a teaching tool.
Keywords: fractional mathematical model; fuzzy fractional mathematical model; coronavirus; Simulink